Tom Clancy under fire - Blackwood, Grant (Clancy, Tom, 1947-2013. Jack Ryan, Jr., 2015)
"On a routine intelligence gathering mission in Tehran, Jack Ryan, Jr., has lunch with his oldest friend, Seth Gregory, an engineer overseeing a transcontinental railway project. As they part, Seth slips Jack a key, along with a perplexing message. The next day Jack is summoned to an apartment where two men claim Seth has disappeared--gone to ground with funds for a vital intelligence operation. Jack's oldest friend has turned, they insist. They leave Jack with a warning: If you hear from Seth Gregory, call us immediately. And do not get involved. But they don't know Jack. He won't abandon a friend in need. His pursuit of the truth will lead him across Iran, through the war-torn Caucasus, and finally deep into territory coveted by the increasingly aggressive Russian Federation. Along the way, Jack is joined by Seth's primary agent, Ysabel, a enigmatic Iranian woman who seems to be his only clue to Seth's whereabouts. Jack soon finds himself lost in a maze of intrigue, lies, and betrayal where no one is who they seem to be--not even Seth, who's harboring a secret of his own that harkens back to the Cold War. A secret that is driving him to the brink of treachery. Racing against the clock, Jack must unravel the mystery: Who is friend and who is foe? Before it's over, Jack Ryan, Jr., may have to choose between his loyalty to Seth and his loyalty to America"--